Analisis Transfer Pricing Determinants Di Masa Pandemi Covid-19: Suatu Studi Untuk Mengidentifikasi Permasalahan Transfer Pricing Di Indonesia - Meily Surianti; Asriyati Asriyati; Putri Wahyuni; Jojor Lisbet Sibarani; Susilawati Susilawati (Department of Accounting, Faculty of Economics & Business, 2023)
This study aims to measure the effect of company size, profitability, leverage and intangible assets practices transfer pricing. This research was conducted at the Indonesia Stock Exchange (IDX), which is a capital market that is still classified as an emerging market. Each capital market has different characteristics, so it is hoped that the results of this research can be used as a model to understand the symptoms or phenomena that occur as a result of Covid 19 to serve as a basis for policy making for regulators and other related parties. The research population is manufacturing sector companies listed on the IDX with an observation period of 2020-2021, namely during the Covid 19 pandemic. The analysis model uses a multiple linear regression model. The results of this study indicate that profitability has an effect on transfer pricing, while company size, leverage and intangible assets have no effect on transfer pricing.